2018
DOI: 10.3389/fmicb.2018.01894
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Water: A Dynamic Reflection of Antibiotic Resistance Across Landscapes

Abstract: Little is known about the role of surface water in the propagation of antibiotic resistance (AR), or the relationship between AR and water quality declines. While healthcare and agricultural sectors are considered the main contributors to AR dissemination, few studies have been conducted in their absence. Using linear models and Bayesian kriging, we evaluate AR among Escherichia coli water isolates collected bimonthly from the Chobe River in Northern Botswana (n = 1997, n = 414 water samples; July 2011–May 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…Surface water remains a connecting link between the emergence and distribution of antibiotic resistance among pathogens due to direct disposal of fecal and agricultural runoff, and the hospital and municipal wastewater effluents (Grenni et al, 2018). Once the antibiotic resistance bacteria enters the waterways, they can either be consumed by humans or animals and can cause infections, or they can transfer ARGs to other bacteria which are present in that environment (Sanderson et al, 2018). In Sikkim, to maintain the continuity of water supply to the community, spring water is being collected and supplied to the community via pipelines.…”
Section: Discussionmentioning
confidence: 99%
“…Surface water remains a connecting link between the emergence and distribution of antibiotic resistance among pathogens due to direct disposal of fecal and agricultural runoff, and the hospital and municipal wastewater effluents (Grenni et al, 2018). Once the antibiotic resistance bacteria enters the waterways, they can either be consumed by humans or animals and can cause infections, or they can transfer ARGs to other bacteria which are present in that environment (Sanderson et al, 2018). In Sikkim, to maintain the continuity of water supply to the community, spring water is being collected and supplied to the community via pipelines.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported wildlife species as potentially important reservoirs of resistant microorganisms and resistance genes [ 19 , 20 ]. For example, Escherichia coli isolates producing extended spectrum beta-lactamases (ESBL) have been isolated from wild boar ( Sus scrofa ) in several European countries [ [21] , [22] , [23] ], putting at stake the efficacy of beta-lactam antibiotics ( e.g. penicillin), which are among the most important class of antimicrobial agents used in human and veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported increased antibiotic resistance in rivers and lakes after rain ( Zhang et al . 2016 ; Sanderson et al . 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…2010 ; Middleton & Salierno 2013 ; Kumar et al . 2018 ; Sanderson et al . 2018 ) and seawater ( Cooke 1976 ; Rabbia et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation